Pink Labor on Golden Streets Queer Art Practices - Erharter, Christiane; Schwärzler, Dietmar; Sircar, Ruby; Scheirl, Hans (Publication Series of the Academy of Fine Arts Vienna, 2015)
Pink Labor on Golden Streets. Queer Art Practices is particularly concerned with combining, juxtaposing, or playing off various artistic strategies where form and politics intervene. Two artistic attitudes, often perceived as divergent, are described here: the choice of form attributed to political issues versus political stances dictating the question of form. This book sheds light on contradictory standpoints of queer art practices, conceptions of the body, and ideas of "queer abstraction," a term coined by Judith Jack Halberstam that raises questions to do with (visual) representations in the context of gender, sexuality, and desire. Pink Labor on Golden Streets builds on an exhibition and a conference that took place at the Academy of Fine Arts Vienna in 2012. The contributions in this book expand on these ideas and practices through interviews, essays, collages, as well as personal and academic texts.